FACTORS DETERMINING THE PLACE OF DISCOURSE IN ADVERTISING TEXT AND ITS INFLUENCE ON THE SOCIAL STRUCTURE - Begzodbek Abdullaev (Galaxy International Interdisciplinary Research Journal, 2021)
The article examines one of the topical issues of linguistics, concerning the understanding of discourse from the point of view of the basic paradigm "text - discourse". The features of the language of advertising texts in the context of discursive parameters are revealed.